Analysis and prediction of the cutting forces of three dimensional end milling using finite elements modelling - Gebremariam, Mebrahitom Asmelash; Saptaji, Kushendarsyah; Mohd Azmir, Mohd Azhari; Zamzuri, Hamedon; Ahmad Razlan, Yusoff; Muhammed Nafis, Osman Zahid (2020)
Aluminium alloy 6061 is one of the versatile material which is commonly used in the transportations, part component in machineries and medical equipment and because of its range of mechanical strength and toughness properties and very good corrosion resistance in its industrial applications [1-3]. Although it has a considerable very good machinability compared to other similar materials, it is reported that machine shops have a number of specific concerns when it comes to working with this material, including long, stringy chips, chips wrapping on parts, machined surface finish, rough thread finish, dimensions [4]. This calls for the machining predictions and appropriate use of machining parameters. End milling is one of the common methods in machining of aluminium 6061 because of its capability and versatility to produce various profiles, curve, and surfaces. The quality of end milling machining is affected by the geometry and of cutting flutes and the surface of the end mill.